(untitled) (Educação e Pesquisa, 2006)
This article offers a review of the literature about the organization of schooling in cycles in Brazil, pointing out the aspects that have been emphasized, the limitations and perspectives for the research on this topic. The review covered 147 texts, which were classified into five categories: (a) discussions of theoretical aspects related to cycles in school; (b) production and formulation of policies; (c) implementation of policies; (d) analysis of results of policies and impact on the performance of pupils; and (e) literature review. It is argued that the nature of policies and the analysis of the development of the discourse of these policies are aspects that have been neglected by the research about cycles. Apart from that, it is argued that the following aspects have been little explored: (a) the analysis of the implementation of the policy at school and in the classroom through observations and ethnographic research; (b) the analysis of the trajectory of the policies from their formulation to their implementation in the classroom; (c) studies including the opinion of managers and policymakers involved with schooling in cycles. The conclusion presents aspects that deserve to be studied in greater depth to bring about a clearer, wider, and more critical understanding of the cycles at Brazilian schools.